Analysis of Vocational High School Students’ Learning Styles in the Implementation of the Merdeka Curriculum - Anisa Ayu Lestarina; Durinda Puspasari (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The implementation of the Merdeka Curriculum emphasises differentiated instruction and student-centred learning, requiring teachers to understand students’ diverse learning characteristics. However, the integration of learning styles into classroom practices remains limited, particularly in vocational education contexts. Objective: This study aims to analyse the learning styles of tenth-grade students in the Office Automation and Governance (OTKP) program, identify challenges in implementing learning styles within the Merdeka Curriculum, and examine strategies to address these challenges. Method: This study employs a qualitative descriptive approach. Data were collected through interviews and documentation using purposive sampling, involving the principal, vice principal for student affairs, teachers, and students. Data validity was ensured through source triangulation, and data were analysed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Results: Students exhibit varied learning styles, with a dominant tendency toward auditory learning. The challenges identified include limited flexibility in students’ use of multiple learning styles, insufficient teacher understanding of differentiated instruction within the Merdeka Curriculum, and inadequate supporting learning facilities. To address these issues, teachers have implemented various strategies, including diversifying instructional methods, using visual media, and applying project-based learning. Conclusion: Although the Merdeka Curriculum has been implemented structurally, its pedagogical application has not yet fully accommodated students’ diverse learning styles, resulting in a gap between policy expectations and classroom practices. Contribution: This study contributes to the existing literature by emphasising the importance of integrating learning style analysis into differentiated instruction. It provides empirical insights for developing adaptive teaching strategies in vocational education settings.